PENGARUH PENGUNGKAPAN FAKTOR RISIKO TERHADAP INITIAL RETURN DARI INITIAL PUBLIC OFFERING (STUDI EMPIRIS PADA PERUSAHAAN IPO PADA 2017 DAN 2018 YANG MENERAPKAN POJK NO. 8/POJK.04/2017) - Esha Strnadiva; Andrian Budi Prasetyo (Diponegoro Journal of Accounting, 2019)
This study investigate the effect of risk factor disclosure which has been This study investigate the effect of risk factor disclosure which is in prospectus to first day of Initial Return in first day of secondary market. Risk Factor disclosures measured by index based on POJK no. 8/POJK.04/2017. There are four independent variables based on this regulation, those are primary risk diclosure, general risk disclosure, business risk diclosure, dan risk for investor disclosure. Initial Return is measured by calculation of closing price at the first day of secondary market substracted by offering price and then divided by offering price. The data used in this study obtained from the issuer’s prospectus that IPO on 2017 and 2018 and use POJK number 8/POJK.04/2017 as their prospectus’s standard. The issuers that apply this standard are seen based on the date of the Registration Statement. The issuers that have regristation statment’s date after March 14th, 2017 is consider using POJK number 8/POJK.04/2017.  Samples were collected by purposive sampling method, and analyzed by multiple linear regression. The results indicate that disclosure of primary risk, business risks, and risks for investors does not affect the initial return of IPO. While the general risk disclosure negatively affects IPO initial return.